Early Complications after Thyroid Surgery - Balsam Waleed Hussain Al-Askari (Institute of Medico-legal Publications Pvt Ltd, 2021)
Background: In this study we shall deal with the early complications after thyroid surgery and compare the complication rate with the extent of resection (subtotal, near total and total thyroidectomy). Patients and Methods: Early complications after thyroid surgery were studied in A prospective study in One hundred patients. Data was collected in the pre-designed proforma. And they are classified according to age and sex of the patients, clinical conditions and training state of the surgeon. Descriptive statistics was used to calculate frequency of each complication in the early post-thyroidectomy period. Results: Most of the patients were females and lie at the (30-39) age group. Clinically, most of them are presented with simple multinodular goitre. Subtotal thyroidectomy is the most commonly used type of resection. The frequency of complications after total thyroidectomy is more than other types. And identification of the (RLN) will minimize the incidence of injury. These complications were (4%) tension haematoma, (11%) hypocalcaemia, (4%) respiratory obstruction, (8%) developed recurrent laryngeal nerve paralysis, (2%) superior laryngeal nerve paralysis, and (1%) wound infection. Surgeon’s experience is so important, in which there is less complications when the operation is performed by a consultant surgeon. Conclusions: Surgery may be associated with significant numbers of post-operative complications according to the type of surgery. Total thyroidectomy confers certain advantages over less extended procedures, but it is associated with higher morbidity. Due to the risk of an unsuspected malignancy and goiter relapse following conservative surgery and increased risk of complications following reoperation, total thyroidectomy is emerging as an attractive surgical option.